Factors influencing the SME business success in Malaysia - Lim, Chin Hui; Teoh, Kok Ban (Annals of Human Resource Management Research, 2021)
Purpose: The research aimed to investigate the factors that influence SME business success in Malaysia. Research methodology: This study employed a quantitative research design and used a paper-based online questionnaire to collect data from 100 SME entrepreneurs in Malaysia. Smart PLS 3.2.8 was used to analyse the data collected in this study. Results: The study concluded that the factors of entrepreneurs’ personalities traits and effective marketing have no significant relationship with SME business success, while the strategic planning and management is significantly positive related to SME business success. Limitations: The present study had a small number of respondents to obtain more accurate results. Contribution: The results can be useful to optimise the local SME business performance by presenting the factor that is significantly and positively influencing business success. This study makes a new attempt to demonstrate the effect of strategic planning and management on SME business success in Malaysia. Besides, the research emphasises the importance of implementation of strategic planning and management in SME business to enhance the rate of business success. Keywords: Business success, Malaysia, SME